Game of loans : the rhetoric and reality of student debt - Akers, Beth, 1983- (Book collections on Project MUSE., 2016)
"Bringing needed clarity to an issue that concerns all of us, Beth Akers and Mathew Chingos cut through the sensationalism and misleading rhetoric to make the compelling case that college remains a good investment for most students. They show how, in fact, typical borrowers face affordable debt burdens, and argue that the truly serious cases of financial hardship portrayed in the media are less common than the popular narrative would have us believe. But there are more troubling problems with student loans that don't receive the same attention. They include high rates of avoidable defaults by students who take on loans but don't finish college - the riskiest segment of borrowers - and a dysfunctional market where competition among colleges drives tuition costs up instead of down. Persuasive and compelling, Game of Loans moves beyond the emotionally charged and politicized talk surrounding student debt, and offers a set of sensible policy proposals that can solve the real problems in student lending"--